Efficacy of Vedolizumab in Fistulising Crohn's Disease: Exploratory Analyses of Data from GEMINI 2. (17th February 2018) - Feagan, Brian G; Schwartz, David; Danese, Silvio; Rubin, David T; Lissoos, Trevor W; Xu, Jing; Lasch, Karen
Abstract: Background and Aims: Medical management of fistulising Crohn's disease [CD] is constrained by the limited number of available therapies. We evaluated the efficacy of vedolizumab, a gut-selective α4 β7 integrin antagonist approved for treating moderately to severely active CD, in a subpopulation of patients with fistulising CD who participated in the GEMINI 2 trial [NCT00783692]. Methods: Exploratory analyses of data from the GEMINI 2 trial were conducted in 461 responders to 6-week vedolizumab induction therapy who received maintenance placebo [ VDZ/PBO, N = 153] or vedolizumab [ VDZ/VDZ, N = 308]. Fistula closure rates were assessed at Weeks 14 and 52, and the time to fistula closure was analysed by the Cox proportional hazards model with adjustments for significant covariates. Results: At entry into the maintenance period, 153 [33%] patients had a history of fistulising disease and 57 [12%] patients had ≥1 active draining fistula. By Week 14, 28% of VDZ/VDZ -treated patients compared with 11% of VDZ/PBO -treated patients (95% confidence interval [CI], –11.4 to 43.9) achieved fistula closure. Corresponding rates at Week 52 were 31% and 11% (absolute risk reduction [ARR]: 19.7%; 95% CI, –8.9 to 46.2). Similarly, VDZ/VDZ -treated patients had faster time to fistula closure and were more likely to have fistula closure at Week 52 [33% vs 11%; HR: 2.54; 95% CI, 0.54–11.96]. Prior failure of antibiotic therapy was a negative predictor of fistula closure [HR: 0.217; 95% CI, 0.059–0.795; p = 0.021], whereas trough vedolizumab concentrations did not affect closure rates. Conclusions: Our findings are consistent with the beneficial effect of vedolizumab treatment for fistulising CD.